Transactions in Kinship Adoption and Fosterage in Oceania (ASAO monograph ; no. 4) - Brady, Ivan (ASAO Monograph Series, 1976)
A collection of essays that follows up on "Adoption in Eastern Oceania" by Vern Carroll. Most were presented at a symposium during the First Annual Association for Social Anthropology in Oceania (ASAO) meeting in 1972.